Dissemination And Tax Knowledge Analysis On Tax Compliance - Suwailim, Ghozy Tsaqif; Anwar, Muhkamat; Purnomo, Eko (Politeknik Keuangan Negara STAN, 2023)
The level of tax compliance in Tanah Laut, South Kalimantan, was the subject of this study. Several factors influence tax compliance, including dissemination and tax knowledge. The study's goal is to examine and interpret the effects of dissemination and tax compliance variables. The study's population was local taxpayers in Tanah Laut, South Kalimantan, and it was conducted utilizing quantitative research that included experimental and survey methodologies. According to the research findings, dissemination has a considerable favourable effect on tax compliance. Tax knowledge has a small but positive impact on tax compliance. However, the two independent variables have a large impact on tax compliance overall. This research has both practical and theoretical ramifications. To promote tax compliance, the government can implement inclusive policies that consider factors such as income level, simple tax procedures, and good public services.